Application of Demonstration and Practice Methods in Teaching Basic Classical Guitar Techniques for Beginners - Sebelom Kogoya (Musikolastika: Jurnal Pertunjukan dan Pendidikan Musik, 2026)
Objective: This study aims to analyze the implementation of a beginner classical guitar teaching model using a combination of demonstration and practice methods, focusing on improving technical skills, rhythm understanding, and hand coordination. Method: A qualitative descriptive approach with an action research design was employed. Data were collected through direct observation during the learning process, interviews with students, field notes, and documentation over nine learning sessions. The analysis evaluated the development of students’ technical skills and identified challenges arising during the learning process. Results and Discussion: Findings indicate that the gradual combination of demonstration and practice methods effectively enhances students’ technical understanding, including playing posture, hand coordination, apoyando and tirando plucking techniques, and basic rhythm comprehension. Key challenges included finger stiffness, delayed chord transitions, and inconsistencies in plucking patterns. Demonstration provided clear visual guidance, enabling accurate imitation of techniques, while practice fostered motor memory through systematic repetition, supporting gradual and consistent skill improvement. Conclusion: The integration of demonstration and practice methods proved effective for beginner classical guitar learning. This approach not only enhances technical skills but also builds students’ confidence in instrument performance, demonstrating that the combination of visual modeling and hands-on practice is an effective pedagogical strategy in basic music education.